The Theology of Paul the Apostles - Pathrapankal, Joseph (Journal of Dharma, 2020)
James D.G.Dunn, The Theology of Paul the Apostles Michigan/Cambridge: William B. Eerdmanns Publishing Company, Grand Rapids, 1998; pp. xxxvi+808, Hardcover, 45.00.